2008
DOI: 10.2137/145960609789267560
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation and genetic stability of Dendranthema grandiflora Tzvelev in vitro cultures

Abstract: Shoots apices of different chrysanthemum species and varieties have been cryopreserved following different procedures, which are reviewed and compared in this paper. The results obtained are not only methoddependant but also cultivar-dependant. When several methods were compared with a cultivar best results were generally obtained with vitrification procedures than with encapsulation-dehydration. Not much attention has been given to the stability of the recovered chrysanthemum shoots but there are indications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the past it was not possible to completely maintain the stability of chrysanthemum stored in LN, either by using classical/two-step freezing (Fukai and Oe 1990;Fukai et al 1994), as well as by modern vitrification-based techniques (Martín and González-Benito 2009;Martín et al 2011). Our study showed that the encapsulation-dehydration technique based on 14-day preculture with 0.09 M sucrose and 10 µM ABA, followed by 4-day osmotic dehydration and 3-hour desiccation is optimal for the shoot tip cryopreservation of three chrysanthemum cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…In the past it was not possible to completely maintain the stability of chrysanthemum stored in LN, either by using classical/two-step freezing (Fukai and Oe 1990;Fukai et al 1994), as well as by modern vitrification-based techniques (Martín and González-Benito 2009;Martín et al 2011). Our study showed that the encapsulation-dehydration technique based on 14-day preculture with 0.09 M sucrose and 10 µM ABA, followed by 4-day osmotic dehydration and 3-hour desiccation is optimal for the shoot tip cryopreservation of three chrysanthemum cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the bead protects the explants from the toxic influence of concentrated sucrose solutions and allows for their desiccation to low moisture content (Engelmann 2008). However, previous studies with chrysanthemum encapsulation-dehydration have been rather unsatisfactory, resulting in low survival (20-45%) or poor regrowth rates (12%) and regeneration of multiple shoots through callus (Halmagyi et al 2004, Martin and Gonzalez-Benito 2009.…”
Section: Introductionmentioning
confidence: 99%